A multicenter study on anaphylaxis caused by peanut, tree nuts, and seeds in children and adolescents. Issue 3 (12th January 2017) - Jeong, K.; Lee, S.‐Y.; Ahn, K.; Kim, J.; Lee, H.‐R.; Suh, D. I.; Pyun, B.‐Y.; Min, T. K.; Kwon, J.‐W.; Kim, K.‐E.; Kim, K. W.; Sohn, M. H.; et al.
Abstract: Peanut (PN) and tree nuts (TNs) are common causes of anaphylaxis in Western countries, but no information is available in Korea. To feature clinical characteristics of anaphylaxis caused by PN, TNs, and seeds, a retrospective medical record review was performed in 14 university hospitals in Korea (2009–2013). One hundred and twenty‐six cases were identified, with the mean age of 4.9 years. PN, walnut (WN), and pine nut accounted for 32.5%, 41.3%, and 7.1%, respectively. The median values of specific IgE (sIgE) to PN, WN, and pine nut were 10.50, 8.74, and 4.61 kUA /l, respectively. Among 50 cases managed in the emergency department, 52.0% were treated with epinephrine, 66.0% with steroid, 94.0% with antihistamines, 36.0% with oxygen, and 48.0% with bronchodilator. In conclusion, WN, PN, and pine nut were the three most common triggers of anaphylaxis in Korean children, and anaphylaxis could occur at remarkably low levels of sIgE.